Exploring Environmental Mitigation Strategies for CO2 Emissions in OECD Countries: Does Geopolitical Risk Affect Their Effectiveness? - Zohra, Kahouli; Hasni, Radhouane; Imen, Ouerghi (International Journal of Energy Economics and Policy, 2025)
The World Economic Forum’s Global Risks 2024 report identifies four key strategies for mitigating climate threats: Localized strategies, breakthrough endeavours, collective actions and cross-border coordination. It also highlights the interplay between two major crises: climate and conflict. Consequently, in a world where environmental and geopolitical risks (GPR) are increasingly interlinked, climate strategies must take this complex dynamic into account. In order to assess the effectiveness of the proposed solutions, taking into account their interdependence with GPR, our study analyses the direct impact of environmental policy stringency (EPS), environment-related technologies (ERT), renewable energies (RE) and political globalisation (PG) on CO2 emissions, as well as the direct impact of GPR and its interaction with these solutions. Results, obtained using an ARDL-PMG approach applied to OECD countries during the period 2000-2020, show that these solutions reduce emissions. However, the direct impact of GPR increases emissions, and its interaction with other solutions negates their benefits, ultimately raising emissions. The study proposes policy recommendations and highlights the importance of considering the negative impact of GPR on CO2 emissions, as well as its negative interaction with environmental solutions, in order to increase the effectiveness of proposed measures and ensure that long-term emissions reduction targets are met.